The Efficiency of Clinical Departments in Medical Faculty Hospitals: A Case Study Based on Data Envelopment Analysis - Sebetci, zel; Uysal, brahim (International Journal of Computer Sciences and Engineering, 2025)
The debts of university hospitals have been increasing recently in Turkey. Thus, they should use their financial resources effectively. The aim of this study is to analyze the technical activities of departments at Adnan Menderes University, Training and Research Hospital, Aydın, Turkey. Data were obtained from the statistical records in 2014. Activities were evaluated with Data Envelopment Analysis (DEA), which is a nonparametric method that allows the use of more than one input and output at the same time. The study comprised three sections. In the first section, expenditure, package deficiencies, and Social Security Institution (SSI) deductions were defined as inputs and income was defined as the output. The Banker, Chames, and Cooper (BCC) model, which aims to minimize inputs, was used in this section. “Orthopedics” was found to be the most effective department. In the second section, faculty members, research assistants, room numbers of policlinics, and bed numbers in services were defined as the inputs; the total number of policlinic patients, total number of patients allocated bed, and income were defined as outputs. In this section, the outcome-focused Charnes, Cooper, and Rhodes (CCR) model, which aims to maximize outcomes, was used. “Emergency” and “Child and Adolescent Psychology” were found to be the most efficient departments. In the third section, faculty members, research assistants, room numbers of policlinics, and bed numbers in services were defined as the inputs; the total number of policlinic patients, total number of patients allocated beds, total operation numbers, and income were defined as outputs. In this section, the CCR model was again used. “Thoracic Surgery” was defined as the most efficient department. At the end of the analyses, reference rates were defined for the inefficient departments.